Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The following is a curve in $3$ dimensions:

$$\begin{eqnarray} x & = & \cos(\theta) \\ y & = & \cos(\theta - \pi/3) \\ z & = & \cos(\theta - 2\pi/3) \end{eqnarray}$$

Is the curve a circle?

If it is, what about this curve in $4$ dimensions?

$$\begin{eqnarray} x & = & \cos(\theta) \\ y & = & \cos(\theta - \pi/4) \\ z & = & \cos(\theta - 2\pi/4) \\ w & = & \cos(\theta - 3\pi/4) \end{eqnarray}$$

I don't know if there is something like a circle in $4$-D. If there is, is this curve the $4$-D version of a circle?

P.S.: Is two-dimensional subspace the generalized plane? I want to learn more about this. What should I read?

share|cite|improve this question
First one: – user2468 Aug 22 '12 at 17:41
Probably it is easiest to first show that $x^2+y^2+z^2$ is constant. Then you have show that the points lie on a two-dimensional subspace, which is less obvious. This strategy should work for the 4D case too. – Rahul Aug 22 '12 at 17:42
@JenniferDylan, how did you do this figure? – Sigur Aug 22 '12 at 17:47
@Sigur I used – user2468 Aug 22 '12 at 17:49
@zjk, if you want to take a circle and embed it in a higher-dimensional space without distorting it, you would naturally want it to still lie in a flat two-dimensional portion of the space, in other words, a two-dimensional subspace. Linear algebra would be a useful thing to learn in this context. – Rahul Aug 22 '12 at 18:56
up vote 21 down vote accepted

Here is a simple treatment of the $n$-dimensional case, where the point on the curve is $\vec x = (x_0, \ldots, x_{n-1})$ with $x_i = \cos(\theta-\pi i/n)$.

  1. The curve lies on a sphere.

    We have $x_i^2 = \cos^2(\theta-\pi i/n) = \frac12+\frac12\cos(2\theta-2\pi i/n)$. So $$\|\vec x\|^2 = \sum x_i^2 = \frac n2 + \frac12 \sum \cos(2\theta-2\pi i/n).$$ The latter term is zero because it is the sum of $n$ equally spaced sinusoids (it is equivalently the $x$-component of the sum of $n$ unit vectors equally spaced along the unit circle, or the real part of the sum of the $n$th roots of $e^{2n\theta\sqrt{-1}}$; in either case, the entire thing is zero by symmetry). So $\|\vec x\|^2$ is a constant, $\frac n2$, independent of $\theta$.

  2. The curve lies on a two-dimensional subspace.

    We have $x_i = \cos(\theta-\pi i/n) = a_i\cos\theta + b_i\sin\theta$ for some fixed $a_i$ and $b_i$ independent of $\theta$. Then $\vec x = \vec a\cos\theta + \vec b\sin\theta$. So $\vec x$ lies on the two-dimensional subspace spanned by $\vec a$ and $\vec b$.

Thus, $\vec x$ lies on the intersection of a sphere in $n$ dimensions and a two-dimensional subspace, i.e. a sphere in two dimensions, also known as a circle.

share|cite|improve this answer

If you use basic trigonometric identities, you can show the first set of three equations is a piece of this plane: $y-z=x$.

share|cite|improve this answer
Also, using trig $x^2 + y^2 + z^2 = 3/2.$ So for all $\theta,$ the distance between $(x, y, z)$ and the origin $= \sqrt{3/2}.$ Putting it together sphere $\bigcap$ plane $=$ circle. – user2468 Aug 22 '12 at 17:41
@JenniferDylan Good way to put it :) – rschwieb Aug 22 '12 at 17:49

Using trigonometric identities, we get $$\cos(\theta-\frac\pi3) = \cos\theta\cos\frac\pi3+\sin\theta\sin\frac\pi3=\frac12\cos\theta+\frac12\sqrt3\sin\theta,$$ $$\cos(\theta-\frac{2\pi}3) = \cos\theta\cos\frac{2\pi}3+\sin\theta\sin\frac{2\pi}3=-\frac12\cos\theta+\frac12\sqrt3\sin\theta.$$ Thus, if we write $\gamma=(x,y,z)$ we get $\gamma = v_1\cos\theta + v_2\sin\theta$ with $v_1=(1,\frac12,-\frac12)$ and $v2=(0,\frac12\sqrt3,\frac12\sqrt3)$. Thus, we have at least an ellipse. Moreover, it is easy to check that $v1\cdot v2=0$. Furthermore, $v_1^2 = 1 + \frac14+\frac14=\frac32$ and $v_2^2=\frac34+\frac34=\frac32$; thus the vectors are orthogonal and of equal length, and therefore it is indeed a circle.

In the general case, we have $(v_1)_k = \cos \frac{(k-1)\pi}d$ and $(v_2)_k=\sin \frac{(k-1)\pi}d$, where $d$ is the dimension of the vector space ($d=4$ in your second case). Thus, $$v_1\cdot v_2 = \sum_{k=1}^d\cos\frac{(k-1)\pi}d\sin\frac{(k-1)\pi}d = \frac12\sum_{k=1}^d\sin\frac{(k+1)2\pi}{d} = 0$$ and $$v_2^2-v_1^2 = \sum_{k=1}^d\left(\cos^2\frac{(k+1)\pi}d-\sin^2\frac{(k+1)\pi}d\right) = \sum_{k=1}^d\cos\frac{(k+1)2\pi}{d} = 0,$$ The construction thus gives a circle in any dimension.

share|cite|improve this answer

For at least the three-dimensional case, here's a more mechanical method (i.e. less enlightening than Rahul's nice answer) to verify if your curve is a circle:

We try to evaluate the curvature $\kappa$ and torsion $\tau$ of the given curve. By the fundamental theorem of space curves, a space curve is uniquely determined (up to rigid motions) by $\kappa(s)$ and $\tau(s)$; if, in addition, $\tau(s)=0$ (i.e. the curve is flat) and $\kappa(s)$ is a constant greater than zero, then we know that the space curve is indeed a circle.

Using formula 26 here for the curvature, we have

$$\begin{align*} \kappa&=\frac{\|\mathbf r^\prime\times \mathbf r^{\prime\prime}\|}{\|\mathbf r^\prime\|^3}\\ &=\frac{\left\|\langle-\sin\,\theta,\cos\left(\theta+\frac{\pi}{6}\right),\cos\left(\theta-\frac{\pi}{6}\right)\rangle\times\langle-\cos\,\theta,-\sin\left(\theta+\frac{\pi}{6}\right),\sin\left(\frac{\pi}{6}-\theta\right)\rangle\right\|}{\left\|\langle-\sin\,\theta,\cos\left(\theta+\frac{\pi}{6}\right),\cos\left(\theta-\frac{\pi}{6}\right)\rangle\right\|^3}\\ &=\sqrt\frac23 \end{align*}$$

Using formula 3 here for the torsion, we have

$$\begin{align*} \tau&=\frac{\mathbf r^\prime\times \mathbf r^{\prime\prime}\cdot\mathbf r^{\prime\prime\prime}}{\kappa^2}\\ &=\frac1{2/3}\begin{vmatrix}-\sin\,\theta&\cos\left(\theta+\frac{\pi}{6}\right)&\cos\left(\theta-\frac{\pi}{6}\right)\\-\cos\,\theta&-\sin\left(\theta+\frac{\pi}{6}\right)&\sin\left(\frac{\pi}{6}-\theta\right)\\\sin\,\theta&-\cos\left(\theta+\frac{\pi}{6}\right)&-\cos\left(\theta-\frac{\pi}{6}\right)\end{vmatrix}\\ &=0 \end{align*}$$

(Note that the determinant is easily seen to be zero, since the third row is a multiple of the first.)

Since $\tau=0$, the curve is flat; in addition, since $\kappa=\sqrt{2/3}$, we find that our space curve is a circle with radius $1/\kappa=\sqrt{3/2}$.

share|cite|improve this answer



As $-y=-\cos(\theta-\frac{\pi}{3})=cos(\theta+\frac{2\pi}{3})$,



Now, $\cos3\theta=4cos^3\theta-3\cos\theta$

If $\cos3\theta=a$ and $\cos\theta=t$

So, $x,-y,z$ are the roots of $4t^3-3t-a=0$





Observe that $(x,y,z)$ satisfy a general plane equation $Ax+By+CZ+D=0$ where $A,B,C,D $ constants, not all zeros.

Also, satisfies the equation of the general circle in 3-D, $(x-a)^2+(y-b)^2+(z-c)^2=d^2 $. $a=b=c=0, d^2=\frac{3}{2}$

In case of $x,y,z,w$,

$z=\cos(\theta-\frac{2\pi}{4})=\sin\theta$, $\sqrt2 y=\cos\theta+\sin\theta$, $\sqrt2 w=-\cos\theta+\sin\theta$

So,$x^2+z^2=1$ and $w^2+y^2=1$


Now $\sqrt2 (y+w)=2\sin\theta=2z=>\sqrt 2z=y+w$

Similarly, $y-w=\sqrt 2x$

Observe that $(x,y,z,w)$ satisfies two general plane equations $Ax+By+CZ+Dw=E$ where $A,B,C,D,E $ constants, not all zeros.

Also, satisfies the equation of the general circle in 4-D, $(x-a)^2+(y-b)^2+(z-c)^2+(w-d)^2=e^2 $ . $a=b=c=d=0, e^2=2$

Again, we know $\cos nx=$Real part of $(\cos x+i\sin x)^n=(\cos x)^n+^nC_2(\cos x)^{n-2}(\sin x)^2+^nC_4(\cos x)^{n-4}(\sin x)^4+...$

Observe there is no term containing $=(\cos x)^{n-1}$

As $\cos n(2x-\frac{2r_i\pi}{n})=\cos(2nx-2r_i\pi)=\cos 2nx=C(say)$

So, $\cos (2x-\frac{2r_i\pi}{n})=R_i$(say), where all $r_i$s are distinct integers with $0 ≤r_i< n$ are the roots of the equation


So, $\sum R_i=0$ as the coefficient of $y^{n-1}$ is 0.

If $x_i=\cos (x-\frac{r_i\pi}{n})=>R_i=2(x_i)^2-1$

So, $\sum (2(x_i)^2-1)=0 =>\sum (x_i)^2=\frac{n}{2}$

This is another way of generalization("The curve lies on a sphere") already achieved by Rahul Narain.

share|cite|improve this answer
You need to put some more words and say that you're trying to prove $x^2 + y^2 + z^2 = 3/2$, and that $x, y, z$ satisfy a plane equation (similar wording for the 4D case). – user2468 Aug 22 '12 at 18:19

It is a circle. If you look at the distance from the origin

$$ r = \sqrt{ \cos^2(\theta) + \cos^2(\theta+\frac{\pi}{3}) + \cos^2(\theta+\frac{2\pi}{3}) } $$

which simplifies to $r = \frac{\sqrt{6}}{2} $.

With the 4-dimensional case the distance simplifies to $r=\sqrt{2}$.

I wonder how to prove the general case of

$$ r^2 = \sum_{i=1}^N \left[ \cos^2\left( \theta + \frac{i-1}{N} \pi \right) \right] = \frac{N}{2} $$

share|cite|improve this answer
Constant distance from origin implies a sphere not a circle. See this and this. – user2468 Aug 22 '12 at 18:11
@JenniferDylan: Yes this is correct, and if the curve was an offset circle then the distance would not be constant either. I guess I needed to show that the curve was planar also. – ja72 Aug 22 '12 at 19:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.